Asymmetric Henry Reaction Catalyzed by Novel Chiral Bioxazolines from Tartaric Acid - Balaraman, Kaluvu; Vasanthan, Ravichandran; Kesavan, Venkitasamy (Synthesis, 2012)
Novel C2-symmetric chiral bioxazolines were synthesized in good yields by the fusion of optically active acids with a tartaric acid derivative. Complexes of these products with copper(II) acetate monohydrate were found to be excellent catalysts for the Henry reaction, giving various nitro alcohols in very good yields and up to 84% enantiomeric excess. Although only five-membered chelation is possible with these ligands, they give better enantioselectivities than other bioxazoline ligands that undergo similar coordination.
Keywords: asymmetric catalysis; aldol reactions; heterocyclic compounds; nitro compounds; alcohols